Development and psychometric evaluation of the trauma nurse core competency scale - Wang, Lu; Zhang, Xinping; Zhang, Ping; Zhou, Qian; Wang, Qianning; Cheng, Jing (Frontiers in Public Health, 2022)
Background: Trauma, especially severe trauma, has become a significant public health problem worldwide. This postulates higher requirements on the core competence of trauma nurses. However, limited scales exist to assess it validly and reliably. This study aims to develop and evaluate the psychometric properties of the Trauma Nurse Core Competency Scale (TNCCS). Methods: This study included three stages. First, scale development was based on a broad literature review and two rounds of Delphi expert consultation. Then, a preliminary investigation was conducted, and a formal scale was formed. Last, scale evaluation was based on a cross-sectional study. Content validity and structure validity were used to evaluate the validity of TNCCS. The Cronbach's α coefficient and the split-half reliability coefficient were used to evaluate the reliability of TNCCS. Results: The final scale contained 46 items under three dimensions, which were Knowledge and skills (21 items), Comprehensive literacy (20 items), Professionalism, and physical and mental health(5 items). The Content Validity Index (CVI) of the total scale was 0.980. The goodness-of-fit indices (χ2/df=3.547, RMSEA=0.065, GFI=0.929, CFI=0.912, NFI=0.904, IFI=0.929) signified a good fit for this model. The Construct Reliability (CR) ranged from 0.89 to 0.98, and the Average Variance Extracted (AVE) ranged from 0.62 to 0.69. The Cronbach's α coefficient of the scale was 0.99, ranging from 0.90 to 0.98 for the subscales. The split-half reliability coefficient was 0.84. Conclusions: The TNCCS demonstrated good validity and reliability, and it could be used to assess the core competency of trauma nurses. The present study has valuable implications for nursing managers to take corresponding measures to train and improve the core competence of trauma nurses.